2020
DOI: 10.3390/fi12020037
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends and Advances Towards a Smarter Grid and Smart Cities

Abstract: Taking advantage of new developing technologies, power systems are being developed into smarter grids with the vision of becoming the next-generation electric grid for smart cities. Some of the emerging issues and challenges associated with the development of technologies for smarter grids and smart cities are highlighted in this special issue of the Future Internet journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Moreover, this study showed that those aged above three years had greater improvements in mouth opening than younger patients. This improvement is likely attributed, at least in part, to the fact that the cognitive development of children differs between younger and older age groups, allowing older children to play a more active role during physiotherapy sessions [18,19]. Based on physiotherapy staff observation, older children participate, adhere and comply to exercise therapy and the use of therapeutic modalities better than younger ones due to their ability to grasp the purpose or function of the treatment.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Moreover, this study showed that those aged above three years had greater improvements in mouth opening than younger patients. This improvement is likely attributed, at least in part, to the fact that the cognitive development of children differs between younger and older age groups, allowing older children to play a more active role during physiotherapy sessions [18,19]. Based on physiotherapy staff observation, older children participate, adhere and comply to exercise therapy and the use of therapeutic modalities better than younger ones due to their ability to grasp the purpose or function of the treatment.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Ensuring a reliable supply of high-quality electric energy to consumers is a difficult but necessary task since it is currently impossible to imagine the normal functioning of consumers (from manufactures to homeowners) without electrical energy usage. Therefore, the main parameters of the power supply system efficiency are power supply reliability (PSR) and power quality (PQ) [1], [2]. In turn, power supply reliability mainly depends on the restoration power supply after failures [3].…”
Section: Introductionmentioning
confidence: 99%